Samantha Rose Hill: Hannah Arendt, London: Reaktion Books 2021.: Hannah Arendt – Critical Lives - Dufraing, An (HannahArendt.net, 2022)
The steady rise in popularity of Hannah Arendt’s work and her exceptionally eventful life make it surprising that Reaktion Books have only recently added a biography of Arendt to their Critical Lives series. This series explores the life and work of leading cultural figures of the modern period and already counts over a hundred biographies of artists, writers and philosophers. The author, Samantha Rose Hill, is well placed to now add a biography of Hannah Arendt. She worked as the assistant director of the Hannah Arendt Center for Politics and Humanities at Bard College and as associate professor at the Brooklyn Institute for Social Research. The fact that Hill has extensive experience in discussing Arendt is evident from the book. She manages to translate Arendt’s complex and wide-ranging ideas into an accessible and very readable book